PERBANDINGAN PENGGUNAAN GAS ALAM TERHADAP LPG DALAM MEMENUHI KEBUTUHAN RUMAH TANGGA DI BONTANG - Joko Triyatno (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The purpose of this study is to determine the cost incurred each month when using natural gas and LPG in meeting household needs. From the research data obtained that the users of natural gas in RT 18 Jl. Brigjend Katamso Bontang has 118 users consisting of 21 RT-1 users, 94 RT-2 users and 3 PK-2 users. For RT-1 users the average cost per month of Rp 106,000 with the use of gas of 17.8 m3, if using LPG 14.3 kg at a cost of Rp. 143,000. and for RT-2 the average expenditure cost per month is Rp 85,800 with the use of gas of 14.3 m3, if using of LPG 11.5 kg at a cost of Rp 115,000. As for PK-2, using natural gas for business activities costs incurred each month an average of Rp 949,200 with the use of natural gas 158.2 m3, if using LPG as much as 127 kg with the cost of Rp. 1.270.000. Expenses incurred will be smaller by opening the channel faucet on the gas pipe is not full. If there is no family event and the number of small family members then the cost is also small is on average Rp 42,000 - Rp 60,000 per month (for the use of natural gas 0 - 10 m3). In addition, the use of natural gas more safe and environmentally friendly, practical and inexpensive compared to using LPG. Keywords: Natural Gas, LPG, Usage, Cost